Worker flows and the impact of labour transitions on earnings in Uganda - Susan Namirembe Kavuma; Oliver Morrissey; Richard Upward (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2015)
The paper examines the flow of workers between employment states, the role of education in these transitions and the impact of the transitions on earnings. It uses panel data for three waves (2005/06, 2009/10 and 2010/11) of household surveys in Uganda. Using the Markov chain process, we estimate transition probability matrices and find bi-directional transitions between formal and informal employment but with a higher tendency of workers to transition from formal to informal than in the opposite direction. When we investigate the relation between education and transitions using probit models, we find the transition from informal to formal increases with education but the movement from formal to informal employment and switching from not working to working declines with education. We further investigate the impact of the transitions on the worker's welfare by estimating wage equations and find evidence for a decline in monthly wages for workers moving from formal to informal employment and a wage gain for workers moving in the reverse direction. We suggest that transitions from informal to formal employment are induced by higher wage offers, while transitions in the opposite direction are more likely to be due to losing a job.
Keywords: J23; J40; O17; O55; 330; formal and informal sector employment; labour transitions